2013
DOI: 10.1016/j.biopsycho.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Detecting violations of temporal regularities in waking and sleeping two-month-old infants

Abstract: Correctly processing rapid sequences of sounds is essential for developmental milestones, such as language acquisition. We investigated the sensitivity of two-month-old infants to violations of a temporal regularity, by recording event-related brain potentials (ERP) in an auditory oddball paradigm from 36 waking and 40 sleeping infants. Standard tones were presented at a regular 300 ms inter-stimulus interval (ISI). One deviant, otherwise identical to the standard, was preceded by a 100 ms ISI. Two other devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…and white-noise sounds. Visual inspection of the ERPs (Figure 2) of Otte et al (2013) suggest that whereas the white noise segments elicited a response pattern that was similar to the typical P150-N250-P350 sequence of deflections (especially in the waking infants), the environmental sounds elicited a P3a-like prolonged positive response in both waking and sleeping infants. Although Otte et al (2013) exercised caution in interpreting this large positive response as a precursor of the adult P3a, Háden et al's (under review) observations regarding differences in contextual processing of noise and environmental sounds in newborns increase the plausibility of their speculative interpretation.…”
Section: Erp Components Observed In the Context Of Acoustic Deviance mentioning
confidence: 96%
See 1 more Smart Citation
“…and white-noise sounds. Visual inspection of the ERPs (Figure 2) of Otte et al (2013) suggest that whereas the white noise segments elicited a response pattern that was similar to the typical P150-N250-P350 sequence of deflections (especially in the waking infants), the environmental sounds elicited a P3a-like prolonged positive response in both waking and sleeping infants. Although Otte et al (2013) exercised caution in interpreting this large positive response as a precursor of the adult P3a, Háden et al's (under review) observations regarding differences in contextual processing of noise and environmental sounds in newborns increase the plausibility of their speculative interpretation.…”
Section: Erp Components Observed In the Context Of Acoustic Deviance mentioning
confidence: 96%
“…2 months of age, morphological differences emerge between the ERPs elicited by rare noise and environmental sounds. Otte et al (2013) adapted the oddball paradigm of Kushnerenko et al (2007) and studied a relatively large group of 2 month old infants. Embedded in a regular sequence of a repetitive complex tone (500 Hz), these authors presented a temporal (interstimulus interval) deviant, as well as rare environmental (dog barking, doorbell ringing, etc.)…”
Section: Erp Components Observed In the Context Of Acoustic Deviance mentioning
confidence: 99%
“…In addition, a number of authors reported an ability of two to six months old infants to remember a tempo and perceive tempo modifications using a head-turn paradigm (Baruch and Drake, 1997;Trainor et al, 2004;Trehub and Hannon, 2009). Thus, these early behavioral responses speak for an ability to detect rhythm and tempo and violation of these temporal patterns have been detected by electroencephalogram studies in two month-old infants (Otte et al, 2013) and in newborns (H aden et al, 2015). Recently, using magnetoencephalography in 9-month-old infants, Zhao and Kuhl (2016) showed that a music intervention in a social environment for one month (12 sessions of 15 min) increased mismatch responses in auditory and prefrontal cortical regions to temporal violation in music and speech.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the broad spatial electrode coverage was chosen for the additional testing described above [35], whereas a reduced set of frontocentral electrodes (F3, Fz, F4, C3, Cz, C4) was of interest for the present analysis. The spatial coverage of these channels is consistent with the frontocentral distribution of the ORN component in adults and children [20] as well as with typical auditory ERP responses in newborn infants [13].…”
Section: Methodsmentioning
confidence: 99%
“…These additional tests were always administered before the current ones and will be reported elsewhere. They included 13 min of homogenous tone sequences with occasional deviations of different types [for description, see [35]] followed by 5 min of EEG recording without any auditory stimulus presentation.…”
Section: Methodsmentioning
confidence: 99%